Characterization of a novel mutation in PAX9 gene in a family with non-syndromic dental agenesis. (November 2016) - Haddaji Mastouri, Marwa; De Coster, Peter; Zaghabani, Aicha; Trabelsi, Saoussen; May, Yosra; Saad, Ali; Coucke, Paul; H'mida Ben Brahim, Dorra
Highlights: First genetic study on Tunisian Family with non-syndromic Tooth agenesis. Identification of a Novel mutation in PAX9 gene. Update on PAX9 mutations. Abstract: Background: Dental agenesis is the most common developmental anomaly in man and may present either as an isolated trait or as part of a syndrome, such as ectodermal dysplasia. Until now, the underlying molecular pathogenic mechanisms responsible for dental agenesis are still largely unknown. Several genetic and molecular studies have demonstrated that at least 300 genes are involved in tooth formation and development, coding for specific transcriptional factors, receptors or growth factors that are expressed at specific developmental stages. Dental agenesis in this respect is believed to result from altered expression of one or more of these factors during initiation and early morphogenesis of the tooth germ, and the first actors identified were MSX1 and PAX9. Design: In this study, we focalized on a Tunisian family with a non-syndromic autosomal dominant form of tooth agenesis. In order to screen for the eventual genetic cause of dental agenesis in this family we sequenced 4 genes; PAX9, WNT10A, MSX1 and AXIN2 using Sanger sequencing. Results: Direct Screening analysis of PAX9 gene, revealed a novel mutation p.Asp200Serfs*13. It consists of a duplication of 5 basepairs leading to a codon stop 13 position downstream. This novel mutation was found in all affected family members. Conclusions: In this report, we present the first genetic study of a Tunisian family with a non-syndromic autosomal dominant form of tooth agenesis, in which we identified in PAX9 gene a novel mutation. It most likely results in nonsense mediated RNA decay and haploinsifficiency that reduce the transactivation capacity of PAX9.